Relationship Between Micronutrient Ferritin, Vitamin D, And Calcium With The Severity Of Diabetic Foot Based On The Wagner-Meggitt Criteria At Adam Malik Hospital - Amalia Puspita Dewi; Mardianto; Nasution, Melati Silvanni (TALENTA Publisher, Universitas Sumatera Utara, 2025)
Background: Diabetic foot is a significant complication for Type 2 Diabetes Mellitus’s (T2DM) patients. Previous studies have linked diabetic foot to micronutrients such as ferritin, vitamin D, and calcium, but there have been no follow-up studies in Medan. Objective: This study aimed to analyze the relationship between levels of ferritin, vitamin D, and calcium with the severity of diabetic foot, as measured by the Wagner-Meggit criteria, in T2DM patients at Adam Malik Hospital. Method: A cross-sectional study with 48 T2DM patients at Adam Malik Hospital from December 2022 to December 2023. Micronutrient levels were measured, and the severity of diabetic foot was assessed using the Wagner-Meggitt classification. Result: The majority of participants (64.6%) were female. High ferritin levels were observed in 91.6% of patients, while 93.75% had low levels of calcium and vitamin D. Bivariate analysis revealed no significant correlations between ferritin, corrected calcium, or vitamin D levels and Wagner grades 2-5 (p=0.515, p=0.646, p=0.377, respectively). Non-parametric correlation analysis showed significant relationships between corrected calcium (p=0.022) and vitamin D (p=0.027) with Wagner grades. Discussion: Among the 48 subjects, bivariate testing found that ferritin levels above 150 ng/ml were not linked to diabetic foot severity. Low calcium levels (below 8.5 ng/dl) were significantly associated with increased severity of diabetic foot (p < 0.03). 93.75% of participants had low vitamin D levels, which also correlated significantly with foot severity (p=0.027). Conclusion: The study concluded that calcium and vitamin D levels correlate with the severity of diabetic foot, whereas ferritin levels do not.